Distinguishing prodromal stage of bipolar disorder and early onset schizophrenia spectrum disorders during adolescence. (May 2019) - Kafali, Helin Yilmaz; Bildik, Tezan; Bora, Emre; Yuncu, Zeki; Erermis, H. Serpil
Highlights : Prodromal symptoms of bipolar disorder and early onset schizophrenia overlap. Subsyndromal manic symptoms and ADHD are more specific for bipolar prodrome. Brief limited intermittent psychotic symptoms are more specific for psychosis prodrome. 12.1% of those with BD are grouped into a psychotic and nonspecific symptom class. 20% of those with EOSSD are grouped into a mood and nonspecific symptom class. Abstract: Prodromal symptoms of bipolar disorder (BD) and early onset schizophrenia spectrum disorder (EOSSD) overlap. To date, there has been no study directly comparing the prodromal stage of both disorders. Thus, the current study is aimed at determining which prodromal symptom clusters differentiate BD and EOSSD. One hundred twenty one adolescents (33 BD-1, 30 EOSSD, 58 healthy controls) were evaluated for the presence of 79 prodromal symptoms, divided into 7 prodromal symptom clusters. Great than 2 subsyndromal manic symptoms and ADHD comorbidity were significantly more specific for BD than schizophrenia; brief limited intermittent psychotic symptoms (BLIPS) were more likely to be part of EOSSD. In contrast, attenuated psychotic symptoms, and negative symptoms were not specifically related to the diagnosis of EOSSD. In conclusion, subsyndromal manic symptoms, BLIPS, and ADHD might be useful for predicting the trajectory of an emerging affective disorder versus schizophrenia and thus valuable for early detection, and intervention strategies.